Pengembangan E-Modul Terintegrasi Proyek Pada Materi Polimer Sintetis Di MAN 1 Kota Bengkulu - Suandi, Nabilla Aprillia Nur; Elvia, Rina; Ginting, Sura Menda (ALOTROP, 2025)
Students’ understanding of synthetic polymer topics was still low due to the abstract nature of the material and the lack of supporting teaching resources. This study focused on developing a project-integrated chemistry e-module on the topic, aiming to produce a valid, practical, and effective learning resource. The development model used was ADDIE, which consisted of analysis, design, development, implementation, and evaluation stages. The validation results showed that the e-module was very feasible in terms of content with a score of 94% and feasible in terms of media with a score of 73%. After revision, the media score increased to 96% with a very feasible category. A small-scale trial involving 12 students of grade XII in the 2024/2025 academic year obtained very positive responses with an average of 94%. The implementation with 27 students of grade XI IPA 1 MAN 1 Bengkulu through pre-test and post-test resulted in an N-Gain score of 0.74 (high category). These findings proved that the developed e-module was effective in improving students’ understanding and was feasible to be used as an alternative chemistry learning resource on synthetic polymers.